Meteorisations: Reading Amílcar Cabral's Agronomy of Liberation. Issue 2 (4th May 2018) - César, Filipa
Abstract: This article reads Amílcar Cabral's much under-studied early soil science as a body of work not dissociable from his project of liberation struggle against Portuguese colonialism in Guinea-Bissau and Cape Verde. Drawing on research situated within an artistic practice, the article explores the definitions of soil and erosion that Cabral developed as an agronomist, as well as his reports on colonial land exploitation and analysis of the trade economy, to unearth his double agency as a state soil scientist and as a 'seeder' of African liberation. Cabral understood agronomy not merely as a discipline combining geology, soil science, agriculture, biology and economics but as a means to gain materialist and situated knowledge about peoples' lived conditions under colonialism. The scientific data he generated during his work as an agronomist were critical to his theoretical arguments in which he denounced the injustices perpetrated on colonised land, and it later informed his warfare strategies. Cabral used his role as an agronomist for the Portuguese colonial government subversively to further anti-colonial struggle. I argue that the results of Cabral's agronomic work – his care for the soil and attention to its processes and transformations – not only informed the organisation of the liberation struggle, but were crucial to the process of decolonisation, understood as a project of reclamation and national reconstruction in the postcolony.